IMPLEMENTASI PENCATATAN KEUANGAN PADA USAHA KECIL DAN MENENGAH: Studi pada Sentra Industri Kripik Tempe Sanan di Kota Malang - Andarsari, Pipit Rosita; Dura, Justita (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
This study aims to determine the application of financial records on small and medium business units (SMEs) because the SME sector is currently the sector that became the government's flagship. The analytical technique used qualitative descriptive analysis, using intepretive paradigm. Data collected through observation and in-depth interviews to informants to see the practice of applying financial records has been presented properly and correctly and refers to the theory of accounting systems associated with general-purpose financial records. There are two forms of accounting practice in SME Sanan - Malang, which is accounting only practiced in the mind / memory and made some accounting records to the preparation of financial statements balance and L / R. The benefits of these two forms of accounting are limited to the control of some business activities. In this case, SMEs still do not have the ability to present complete and appropriate financial information.